Strategies for Islamic Guidance and Counseling Students in Overcoming Academic Procrastination - Awliana; Rofika Duri; Zamratul Aini (Universitas Negeri Medan, 2026)
Academic procrastination is a common phenomenon among college students and is closely related to time management and self-regulation skills. This study aims to identify the strategies used by students in the Islamic Guidance and Counseling Program at UIN Ar-Raniry, Banda Aceh, to overcome academic procrastination. This study employs a qualitative approach using a descriptive-analytical method. The research subjects consisted of five students from the class of 2024 selected through purposive sampling, with the criteria being active students experiencing academic procrastination. Data collection was conducted through observation and in-depth interviews, followed by analysis using NVivo software. The results indicate that all respondents experienced academic procrastination, including delaying the start and completion of assignments, late submission of assignments, a gap between plans and execution, and a tendency to choose more enjoyable activities over completing academic tasks. Contributing factors included internal factors such as fear of failure, perfectionism, low motivation, suboptimal emotional regulation, and mood dependency, as well as external factors such as social media distractions and a busy organizational activity schedule. The impacts experienced by students included increased anxiety, stress, guilt, rushing to complete tasks, and suboptimal academic performance. The strategies students use to overcome procrastination include breaking tasks into smaller parts, setting priorities, creating to-do lists, limiting social media use, reflecting on academic goals, starting with the easiest parts, and training themselves to begin without waiting for the right mood. These findings indicate that academic procrastination is closely linked to time management and self-regulation skills, which need to be continuously developed.